2011
DOI: 10.1111/j.1755-148x.2011.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐methylation profiling distinguishes malignant melanomas from benign nevi

Abstract: DNA methylation, an epigenetic alteration typically occurring early in cancer development, could aid in the molecular diagnosis of melanoma. We determined technical feasibility for high-throughput DNA-methylation array-based profiling using formalin-fixed paraffin-embedded tissues for selection of candidate DNA-methylation differences between melanomas and nevi. Promoter methylation was evaluated in 27 common benign nevi and 22 primary invasive melanomas using a 1505 CpG site microarray. Unsupervised hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 46 publications
1
75
2
Order By: Relevance
“…Interestingly, although disclosed in a small cohort, this epigenetic signature was validated in a larger independent dataset of malignant melanomas from TCGA. Thomas and colleagues used a similar assay to investigate DNA methylation differences between CM and benign nevi [18]. The authors found 145 genes with significant DNA methylation differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although disclosed in a small cohort, this epigenetic signature was validated in a larger independent dataset of malignant melanomas from TCGA. Thomas and colleagues used a similar assay to investigate DNA methylation differences between CM and benign nevi [18]. The authors found 145 genes with significant DNA methylation differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that GPC3 may be a useful early stage biomarker for patients with the early stages of the disease (0 -II) (Nakatsura et al, 2004;Ikuta et al, 2005). Moreover, cyclooxygenase-2 (COX-2) (Chwirot and Kuźbicki, 2007), serum amyloid A (SAA) (Mian et al, 2005;Findeisen et al, 2009) and DNA methylation profiling (Conway et al, 2011) can be used to distinguish between early melanomas and benign nevi.…”
Section: Biomarkers For Early Melanoma Diagnosismentioning
confidence: 99%
“…The group's results have clearly identified a group of genes in a statistically powerful interpretation that can be used to discriminate nevi from melanomas considering their methylation signature. Furthermore, they adapted this highthroughput methylation profiling to FFPE samples, which are generally prepared by pathologists, abundantly available and appropriate for further routine screening [Conway et al, 2011].…”
Section: Localised Hypermethylationmentioning
confidence: 99%